Tashkent state transport university (Международный научный журнал «Инженер», 2026)
This article investigates the correlation between the potential for sand encroachment on a newlyconstructed railway line and the annual precipitation levels. An expert survey was conducted amongspecialists directly and indirectly involved with this issue, alongside a statistical analysis of natural andclimatic winter-spring precipitation over several years in regions where the under-construction railwayintersects dune sands. The annual precipitation data were compared with the occurrence of sand drifts.The results of the expert survey, monitoring of potential railway sand encroachment, and precipitationanalysis are presented. It was established that the manifestation of sandstorms, and consequently thepotential for sand encroachment on infrastructure, is dependent on the amount of rainfall during thewinter-spring period. Utilizing the findings of this research will enable the elimination of unnecessaryannual measures for protecting the new railway line from sand drifts, specifically those related to thestabilization of mobile sands.